Influence of curing conditions on pumice-based alkali activated composites incorporating Portland cement. (November 2021) - Balun, Bilal; Karataş, Mehmet
Abstract: One way to promote sustainability, energy conservation and environmental protection is to produce construction materials by the activation of aluminosilicate precursors with alkalis. Alkali activated materials produced with raw materials containing low calcium such as pumice harden in aggressive conditions. Therefore, determining the optimum curing conditions are of great importance for the evaluation of these materials. The curing conditions of pumice-based alkali activated materials has been reported by a few studies to a limited extend. This paper succinctly discusses the different curing conditions of pumice-based alkali activated composites incorporating ordinary Portland cement (OPC). The precursor raw material consists of 80% pumice and 20% OPC or %100 pumice. The prepared 50 × 50 × 50 mm cubic paste specimens were subjected to different heat-curing temperatures (20 °C, 40 °C, 60 °C, 80 °C, 100 °C and 120 °C) for 24, 48, 72 and 96 h and aging effect (3-28-90 days) was studied. Compressive strength, UPV, dry density, porosity and total water absorption tests were performed after curing processes. Furthermore, SEM/EDX images of the samples were taken to investigate the effect of curing conditions. The results show that OPC addition has increased the compressive strength under all curing conditions. The highest compressive strength was obtained by curing OPC added samples at 100 °C for 72 h. However, as the heat-curing temperature increased samples gained much of strength with less curing duration. Satisfactory compressive strength results can be obtained from samples cured under ambient conditions and especially containing OPC (63 MPa). The specimens containing OPC with the highest compressive strength are also the specimens with the highest density (1.89 g/cm 3 ) due to dense geopolymeric structure. At the same time, as the compressive strength increases the water absorption and porosity values decrease due to the reduced voids. Consequently, experimental findings revealed that the curing conditions influence the mechanical and physical properties of pumice-based alkali activated composites incorporating OPC. Highlights: Curing conditions affected both the mechanical and physical properties of pumice-based alkali activated pastes. The highest compressive strength in P-HCSs was obtained in 90-day specimens exposed to 100 °C for 72 h. The addition of OPC enabled the P–HSCs to gain strength in ambient conditions.